Recent advances in nanomaterial‐assisted electrochemical sensors for food safety analysis - Gu, Ying; Li, Yonghui; Ren, Dabing; Sun, Liping; Zhuang, Yongliang; Yi, Lunzhao; Wang, Shuo (Food frontiers, 2022)
Food safety as a public health issue has aroused worldwide concern. Food safety risks caused by the existence of food safety hazards in food may occur in all stages of the food supply chain. Thus, great emphasis is placed on sensitive, selective, and convenient analytical methods of various food safety hazards in food. At present, nanomaterials are at the forefront of various electrochemical sensing applications. Given their unique physical, chemical, and biological characteristics, nanomaterials are considered perfect candidates for the design of electrode surface to construct electrochemical sensors with excellent analytical performance. With the assistance of nanomaterials, electrochemical sensors are a potential alternative to conventional methods of food safety analysis. This review focuses on current research achievements of nanomaterial‐assisted electrochemical sensors for food safety analysis reported in recent 5 years. It highlights the different detection mechanisms for analytes, flexible sensing strategies based on nanomaterials, and portable miniaturized electrochemical devices. Finally, the challenges and limitations in the design of electrochemical sensors for food safety analysis are also discussed. This review focuses on current research achievements of nanomaterial‐assisted electrochemical sensors for food safety analysis reported in recent years. It highlights the different detection mechanisms for analytes, flexible sensing strategies based on nanomaterials, and portable miniaturized electrochemical devices. Finally, the challenges and limitations in the design of electrochemical sensors for food safety analysis are also discussed.